The role of impaired adipogenesis in insulin resistance among non-obese individuals - Almuraikhy, Shamma; Alser, Maha; Naja, Khaled; Anwardeen, Najeha; Taha, Samir; John, Jomon; Halim, Sharique; Badran, Saif; Ahmed, Mohamed Badie; Jarrar, Salma; Aljassem, Ghanem; Al-Mohannadi, Fatima Saoud; et al. (Frontiers in Physiology, 2026)
IntroductionAdipogenesis is an essential process for energy storage, hormone regulation, and overall metabolic health. Previous work showed that impaired adipogenesis plays an important role in the development of obesity-associated insulin resistance. This project investigates the role of impaired adipogenesis in the development of insulin resistance among non-obese (lean/overweight) individuals under physiological and pathological microenvironments.MethodsSubcutaneous adipose tissue samples were obtained from insulin-sensitive and insulin-resistant non-obese cohorts undergoing maxillofacial or body contouring surgeries. Preadipocytes were isolated and examined for proliferation and adipogenic capacity, insulin signaling, and inflammatory markers. These assessments were conducted under basal conditions and following treatment with either tumor necrosis factor alpha (TNF-α) to induce insulin resistance or metformin to promote insulin sensitivity.ResultsInsulin-resistant participants, in comparison to insulin-sensitive counterparts, showed lower adipogenic capacity, higher susceptibility to the anti-adipogenic and pro-inflammatory effect of TNF-α potentially due to hyperphosphorylation of insulin receptor substrate-1.DiscussionThis highlights the role of impaired adipogenesis in the pathogenesis of insulin resistance among non-obese individuals. Further research is needed to understand the impact of impaired adipogenesis and the potential therapeutic interventions targeting adipogenesis to improve insulin sensitivity in non-obese individuals.